Pengembangan Kemampuan Kreativitas Dalam Pembelajaran IPS - Amini, Amini; Sahfitri, Anggi Ayu; Fadillah, Allya; Lubis, Kamalia; Mahyuni, Lela; Abdi, Khoirul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Field applications show that social science education is still mainly at the theoretical level. Even the attitude that social studies education is only "as a rote lesson" is only partially responded to by teachers who solely concentrate on the purpose of providing content in the form of theory. The learning process that takes place in the classroom shows that education in schools has not been able to optimize students' creative thinking abilities, especially in using these abilities to solve the challenges they face everyday. To encourage student creativity, teachers must have their own creative skills. If the teacher acts as a creative pilot for the class, student creativity will also emerge. To fulfill the real social studies educational goals, the subject matter that has been arranged in the syllabus must be well developed. New ideas or ideas that have never been thought of before are considered creative. In the field of education, creativity is very important to understand the lesson or understand all the upcoming assignments. For this reason, efforts must be made to foster creativity starting from elementary school or from an early age. Creative expression and actualization of personal identity in relation to oneself, nature and others is an experience. Keywords: Creativity Ability, Social Studies Learning